ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015 - 2017) - Nadya Dinda P.M Kusuma, 15.05.52.0015; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This reasearch aims to analyze and provide empirical evidence of the influence between institutional ownership, audit committees, executives character, firms size, sales growth and leverage for tax avoidance to manufacturing companies that registered in Indonesia Stock Exchange (IDX) 2015-2017. From the selection of the sample using purposive sampling method obtained 45 manufacturing companies that could be sampled. This study uses a multiple linear regression analysis. Based on the results of testing the hypothesis it was found that institutional ownership positive significant affect on tax avoidance, audit committees has no effect on tax avoidance, firm size and leverage positive doesn’t has significant on tax avoidance, excecutive character and sales growth negatively significant affect on tax avoidance. Keywords: tax avoidance, institutional ownership, audit committees, executives character, firms size, sales growth, leverage.